Role of cyclooxygenases 1 and 2 in the modulation of neuromuscular functions in the distal colon of humans and mice. Issue 5 (14th April 2005) - Fornai, M; Blandizzi, C; Colucci, R; Antonioli, L; Bernardini, N; Segnani, C; Baragatti, B; Barogi, S; Berti, P; Spisni, R; Del Tacca, M
Abstract : Background: Cyclooxygenase isoforms (COX-1, COX-2) may exert differential regulatory actions on enteric motor functions under normal or pathological conditions. Aims: To examine the occurrence and functions of COX-1 and COX-2 in the neuromuscular compartment of normal distal colon using human and murine tissue. Methods: Gene expression (human, mouse), protein expression (human), gene deletion (mouse), and the effects of dual and isoform specific COX inhibitors on in vitro motility (human, mouse) were investigated. Results: Reverse transcription-polymerase chain reaction (RT-PCR) showed mRNA expression of COX-1 and COX-2 in human and wild-type mouse colonic muscle whereas only COX-2 or COX-1 was detected in COX-1 or COX-2 knockout animals. Immunohistochemistry localised both isoforms in neurones of myenteric ganglia, COX-1 in circular layer myocytes, and COX-2 in longitudinal muscle. Indomethacin (COX-1/COX-2 inhibitor), SC-560 (COX-1 inhibitor), or DFU (COX-2 inhibitor) enhanced atropine sensitive electrically induced contractions of human longitudinal muscle. The most prominent actions were recorded with indomethacin or SC-560 plus DFU. These results were confirmed under pharmacological blockade of non-cholinergic nerves. Atropine sensitive contractions evoked by carbachol in the presence of tetrodotoxin were enhanced by indomethacin or DFU but not by SC-560. In wild-type mice, contractile responses to electrical stimulation were enhanced by indomethacin, SC-560, or DFU. SC-560 potentiated electrically induced contractions in COX-2, but not COX-1, knockout mice. In contrast, DFU enhanced the contractions elicited by electrical stimuli in COX-1, but not in COX-2, knockout mice. Conclusions: These results indicate that COX-1 and COX-2 are expressed in the neuromuscular compartment of normal human colon where they modulate cholinergic excitatory control of colonic motility at prejunctional and postjunctional sites, respectively.